Bushfire Smoke in Our Eyes: Community Perceptions and Responses to an Intense Smoke Event in Canberra, Australia - Williamson, Rebecca; Banwell, Cathy; Calear, Alison L.; LaBond, Christine; Leach, Liana S.; Olsen, Anna; Walsh, Erin I.; Zulfiqar, Tehzeeb; Sutherland, Stewart; Phillips, Christine (Frontiers in Public Health, 2022)
The 2019–20 bushfires that raged in eastern Australia were an overwhelming natural disaster leading to lives lost or upended, and communities destroyed. For almost a month, Canberra, Australia's capital city in the Australian Capital Territory (ACT), was obscured by smoke from fires which threatened the outer suburbs. While smoke itself is experientially different from many natural disasters, it nevertheless poses a significant public health threat. As the impact of extended bushfire smoke in an urban setting is relatively unexplored we aimed to capture the individual and community-level experiences of the event and their importance for community and social functioning. We responded rapidly by conducting semi-structured interviews with a range of Canberra residents who, due to their personal or social circumstances, were potentially vulnerable to the effects of the smoke. Three major themes emerging from the narratives depicted disruption to daily life, physical and psychological effects, and shifting social connectedness. This study highlighted the ambiguous yet impactful nature of a bushfire smoke event, and identified four simple key messages that may be critically relevant to policy making in preparation for similar smoke events in the future.